2005
DOI: 10.1021/jp053154f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Interstitials in Superconducting La2CuO4:  Their Valence State and Role

Abstract: The nature of the much debated valence state of an interstitial oxygen atom in oxygen-doped La2CuO4 is the subject of this paper. In model cluster calculations, we studied the position, charge, and spin state of the interstitial oxygen atoms in this superconductor. The models considered allow the interstitial oxygen to move off a symmetrical position, to have varying spin and charge, and to be surrounded by various magnetic environments. UB3LYP calculations show that a model having an interstitial oxygen atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Precedent exists in the literature for unusually charged oxygen species in these and related systems. Lee and Hoffmann discussed the possibility of interstitials with peroxide- or subperoxide-like character in the isostructural cuprate La 2 CuO 4 , and Demourgues et al suggested for highly hyperstoichiometric samples of La 2 NiO 4+δ (δ ≈ 0.25) the association of interstitial defects with axial oxygen sites, forming O 3 5– polyoxide clusters . On the other hand, the 17 O NMR shift of the O i resonance does not appreciably change between x = 0 and in any of the Sr-substituted samples, whereas any change in the peroxide-like character of O i would be expected to alter the nuclear shielding and thus the observed NMR shift. , Therefore, covalency changes involving the interstitial sites would seem unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Precedent exists in the literature for unusually charged oxygen species in these and related systems. Lee and Hoffmann discussed the possibility of interstitials with peroxide- or subperoxide-like character in the isostructural cuprate La 2 CuO 4 , and Demourgues et al suggested for highly hyperstoichiometric samples of La 2 NiO 4+δ (δ ≈ 0.25) the association of interstitial defects with axial oxygen sites, forming O 3 5– polyoxide clusters . On the other hand, the 17 O NMR shift of the O i resonance does not appreciably change between x = 0 and in any of the Sr-substituted samples, whereas any change in the peroxide-like character of O i would be expected to alter the nuclear shielding and thus the observed NMR shift. , Therefore, covalency changes involving the interstitial sites would seem unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Two key predictions of this mechanism have been confirmed, one by direct measurement [ 74 ], which shows that substitution of Cu by Zn reverses the orbital transition locally, and the other by calculations [ 58 , 86 ], which show that the dopant charge remains localized in its vicinity, i.e., does not reach the planes physically—the charge redistribution around the dopant is found to be neutral overall within a single spacer layer. At first sight, the above metallization of the Cu–O ionic bond would give rise to a mixture of Cu and Cu configurations in the plane, bathed by a Fermi liquid of oxygen hole carriers.…”
Section: Microscopic Featuresmentioning
confidence: 98%
“…The metallic alloying scenario, wherein the planes are doped with delocalized dopand holes, is contradicted by ab initio calculations showing that the Sr hole in La 2−x Sr x CuO 4 remains localized [14]. It is similarly found that the interstitial oxygen in La 2 CuO 4+δ preferentially creates an inert peroxide, O 2− 2 , with the apical oxygen [15]. A more remote possibility, the impurity-band scenario, is excluded experimentally [16].…”
Section: Introductionmentioning
confidence: 99%